Produção de biossurfactantes utilizando resíduos agroindustriais como substrato - Bueno, Gisele Ferreira [UNESP] (2014)
Biosurfactants are produced from microorganisms and are compounds with low toxicity and high biodegradability with ability to reduce surface and interfacial tensions. Due to the advantage of being more biodegradable compared to the chemical origin ones, they are more suitable to be used in different applications. This study aimed to evaluate the biosurfactant production by Bacillus subtilis and Bacillus amyloliquefaciens through distinct substrates in solid state fermentation and use the biosurfactant produced in the biological treatment of industrial wastewater containing oil and grease. Fermentations were performed by Bacillus subtilis and Bacillus amyloliquefaciens using wheat bran, crueira and sugar cane bagasse as solid substrates. Fermentations took place in plastic bags with 10 grams of solid substrate plus phosphate buffer, manipueira and distilled water (as humidifier solution in order to obtain 40, 60 and 80% humidity) and 1 mL of glycerol or an oil frying (as inductor solution) or distilled water and incubated at 37°C for 48, 72 and 96 hours. Analysis of surface tension, emulsification index, emulsifying activity and crude biosurfactant production (weight) were performed. The results indicate that the microorganism Bacillus amyloliquefaciens produces biosurfactant and is capable of reducing the surface tension to near and even better values than the microorganism Bacillus subtilis. With respect to their use in wastewater treatment systems, no satisfactory results were observed, but no further studies should be discarded for better adaptations to the employed methodologies